2016
DOI: 10.1186/s12889-016-3096-8
|View full text |Cite
|
Sign up to set email alerts
|

Undocumented migrant women in Denmark have inadequate access to pregnancy screening and have a higher prevalence Hepatitis B virus infection compared to documented migrants in Denmark: a prevalence study

Abstract: BackgroundPregnant residents of Denmark are tested by their GP for current infections with Hepatitis B virus (HBV), HIV and syphilis through the Danish pregnancy screening programme to identify infections and initiate interventions to prevent mother-to-child transmission. Documented migrants (DM) have access to this screening but undocumented migrants (UM) do not, instead relying on ad-hoc care from clinics run by non-governmental organisations. We aimed to assess screening frequency in UM and to compare preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
34
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 17 publications
(16 reference statements)
10
34
4
1
Order By: Relevance
“…One major reported obstacle is the pre-donation screening guidelines resulting in a temporal or permanent deferral for a substantive number of potentially rare donors; This result is in line with those of other international studies which report that lower donor eligibility and higher deferral rates are problematic [4,23]. Although the incidence of transmittable diseases is higher among certain migrant groups, especially among people from Sub-Saharan African descent [24,25] excluding potentially rare donors during the preliminary screening steps, the Donor Health Questionnaire and the consultation with the donor physicians, before giving blood samples precludes the identification of persons with rare antigen combinations [26]. In the Netherlands, those with a Sub-Saharan African partner cannot donate immediately, but a survey among various national blood bank organisations had revealed that almost 30% even permanently ban people from Sub-Saharan countries [5].…”
Section: Discussionsupporting
confidence: 65%
“…One major reported obstacle is the pre-donation screening guidelines resulting in a temporal or permanent deferral for a substantive number of potentially rare donors; This result is in line with those of other international studies which report that lower donor eligibility and higher deferral rates are problematic [4,23]. Although the incidence of transmittable diseases is higher among certain migrant groups, especially among people from Sub-Saharan African descent [24,25] excluding potentially rare donors during the preliminary screening steps, the Donor Health Questionnaire and the consultation with the donor physicians, before giving blood samples precludes the identification of persons with rare antigen combinations [26]. In the Netherlands, those with a Sub-Saharan African partner cannot donate immediately, but a survey among various national blood bank organisations had revealed that almost 30% even permanently ban people from Sub-Saharan countries [5].…”
Section: Discussionsupporting
confidence: 65%
“…Although this number could be an overestimation of the actual prevalence, the data included only first-time asylum applicants and did not include undocumented and illegal immigration, which could have an additional effect on the total HBV prevalence in host countries. 47,48 Programmes and strategies HBV vaccination strategies are generally still a controversial issue in the European public health system. Even though the cost-effectiveness of universal infant…”
Section: Panel: Data Analysismentioning
confidence: 99%
“…Moreover, these risks appear aggravated amongst migrant women who do not receive antenatal care during pregnancy [ 32 ]. Increased presence of hepatitis B [ 33 ], human immunodeficiency virus (HIV), diabetes, sexually transmitted infections, hypertonia, headache, and acute stress have also been observed amongst this cohort, when compared to the general population of pregnant women [ 34 ]. An elevated presence of psychopathology has also been observed amongst this group, with post-traumatic stress disorder (PTSD), depression, and anxiety disorders, as well as suicidal ideation and attempts being prevalent [ 34 ].…”
Section: Introductionmentioning
confidence: 99%